The Relationship of Mother’s Knowledge and Attitude toward Primigravida Anxiety in Facing Maternity - Fitriani Fitriani; Yarmaliza Yarmaliza; Teungku Nih Farisni (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2019)
The purpose of this study was to determine the relationship of knowledge and attitude with Anxiety Levels In Mother's first pregnancy. In the first pregnancy Facing Mother Maternity say anxious to pregnancy experienced. Anxiety include anxiety about the state of the self and circumstances fetus. This type research is analytic survey. There is correlation between knowledge, attitude and level of anxiety (P.Value < 0,05). To be a mother searching for rushing in their spare time. So the negative thoughts about labour and childbirth face the anxiety can be transferred to activities that have been more helpful.